Recentivism: its creator and his work - Dura, Adam A. (Folia Philosophica, 2005)
The author explains to the reader the philosophical thought of the creator of recentivism - Professor Józef Bańka. He presents Bańka's original philosophical method a recentiori and the structure of the philosophy of the present, from its ontology and epistemology to its eutyphronic, the ethics of rightmindedness, the ethics of recentivism, the philosophy of history and eurorecentivism. This article can provide for the reader an incentive to explore recentivism and to formulate their own creative interpretations. The author quotes many works of Bańka, in which the Professor presented his opinions. He shows the emerging intellectual possibilities created by recentivism but also some philosophical problems encountered by the recentivism scholars. The question about the place occupied by modern philosophy is being asked more and more frequently. The answer is still to be found, the more so because recentivistic philosophy is invariably in statu nascendi.